2017
DOI: 10.1111/bph.13868
|View full text |Cite
|
Sign up to set email alerts
|

Novel selective PDE type 1 inhibitors cause vasodilatation and lower blood pressure in rats

Abstract: These novel PDE1 inhibitors induce vasodilation and lower BP, suggesting a potential use of these vasodilators in the treatment of hypertension and vasospasm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 39 publications
1
26
0
Order By: Relevance
“…Laursen et al . () similarly demonstrated ODQ‐sensitive relaxation to Lu AF58027 in rat mesenteric arteries pre‐contracted with U46619 and the selective α 1 ‐adrenergic receptor agonist, phenylephrine. Accordingly, PDE1 inhibition potentiated the relaxation induced by the sGC activator BAY 41‐2272, an effect that was abolished with PKG inhibition.…”
Section: Discussionmentioning
confidence: 78%
See 4 more Smart Citations
“…Laursen et al . () similarly demonstrated ODQ‐sensitive relaxation to Lu AF58027 in rat mesenteric arteries pre‐contracted with U46619 and the selective α 1 ‐adrenergic receptor agonist, phenylephrine. Accordingly, PDE1 inhibition potentiated the relaxation induced by the sGC activator BAY 41‐2272, an effect that was abolished with PKG inhibition.…”
Section: Discussionmentioning
confidence: 78%
“…Taken together, our results suggest that PDE1 inhibition mediates relaxation predominantly through the cGMP/PKG pathway. However, the contribution of the AC/cAMP pathway cannot be completely dismissed; a recent study by (Laursen et al ., ) showed that the AC inhibitor, SQ22536, partially inhibited relaxation induced by Lu AF58027 in the rat mesenteric artery.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations